The effect of leaderboard in different goal-setting levels - Chernbumroong S. (2017)
© 2017 IEEE. implementing leaderboard is one of the most popular gamification strategies which allows triggering various types of engagement and potentially links to different performances in skill acquisition and knowledge transfer. Although leaderboards are currently implemented in various domains and many kinds of leaderboards are currently employed, previous studies reported that not all participants engaged with leaderboards will gain positive results. Therefore, it is difficult to argue that all kinds of leaderboards are able to enhance the performance of every people. Since the research in this domain is seldom, this study adopted the goal-setting theory as a framework by which it aims to understand the user's behavior and the effect of leaderboard. Thus, the objective of this paper is to examine the effect of leaderboard in different goal-setting levels. In our experiment, three kinds of leaderboards in different goal-setting levels (Do-your-best leaderboard, Difficult leaderboard, and Impossible leaderboard) were designed and tested with thirty-three students from the Department of Tourism, Faculty of Humanities, Chiang Mai University. The participants were divided into three groups and were assigned to comprehend the topic of Cardiopulmonary Resuscitation (CPR) via a video lecture and online exercise of 40 minutes. The data were collected from the knowledge test (Pre and Post-test) and statistic results from the online exercise. According to the results, we concluded that the 'difficult' leaderboard is appropriate for motivating participants to continue self-practice in each task of online exercise, while 'impossible' leaderboard is able to encourage participants to complete the overall tasks.